PROPERTIES OF CONCRETE CONTAINING RECYCLED AGGREGATE AND WASTE GLASS POWDER - TALUKDER RANA, MD. LUTFAR RAHMAN (Department of Civil Engineering, MIST, 2023)
The coarse aggregate and fine aggregate are replaced by the RBA and WG, respectively. A mix design of a total of fifteen different mixtures is planned with a comprehensive test matrix. Fundamental tests of concrete such as density, gradations, air content, slump, as well as the mechanical properties i.e. compressive strength, splitting tensile strength, and flexural strength of RBA-based WG concrete at different ages are investigated following ASTM standards. Subsequently, a non-destructive test method ultrasonic pulse velocity is also examined to understand the pulse conductivity through produced concrete. For further investigation, a microstructural analysis is also performed using scanning electron microscopy. It is observed that the compressive strength diminishes with a higher amount of reclaimed brick aggregate. In contrast, a 12.5% higher strength can be achieved with the addition of 20% glass content though the strength falls if further glass is added as fine content. Similar trends are observed for the split tensile and flexural strength properties of this RCG. In the SEM, it is observed that up to 20% glass content RCG becomes denser formation with lesser voids; however, the larger voids and fissures are observed as glass content increases. The research has been extended to investigate the flexural behaviour of the RCG in the reinforced concrete beam. Load-deformation of the beam and stress-strain response of the used rebar’s were recorded by a standard data acquisition system including LVDT, strain gauges with a 20-channel data logger. The flexural capacity of RCG-made beams is very much comparable with control beams as the deviation is only in a range of 1%-8% for adding glass content up to 20% replacement. The experimental results are compared with the established codes such as ACI-318-14. The experimental value is near to the theoretical value calculated through the ACI-318-14 code.The outcome of this study may contribute to the application of RBA and WG as ingredients of normal and reinforced concrete.
First and foremost, all praise and profound gratitude goes to the almighty Allah, who is the most beneficent and the most merciful, for allowing the author a great opportunity and the ability to bring this effort to fruition safely and peacefully. The author conveys his heartiest gratitude to his supervisor, Lt Col Khondaker Sakil Ahmed, Ph.D., PEng., CEng. Associate Professor, CE Dept., MIST for his systematic support and supervision of the dissertation. His guidance and suggestions worked as inspiration to unlock different new avenues for research. The author would like to thank Dr. Ataur Rahman, Professor, CE Dept., KUET for the useful comments, remarks, and valuable suggestions. The author is grateful for the technical support provided by the Center for Advisory & Testing Services of the Civil Engineering Department (CATS-CE) of MIST, Dhaka, Bangladesh. The author would also like to acknowledge the contribution of lab technicians of the Concrete and SM lab of the Civil Engineering Department of MIST.